2020
DOI: 10.1002/jaba.709
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus presentation versus stimulus removal in the Good Behavior Game

Abstract: The Good Behavior Game (GBG) is an effective intervention to reduce disruptive behavior. The GBG typically involves immediate stimulus presentation (e.g.., delivery of a token) following disruptions; however, experimenters have also removed tokens contingent upon disruptions. In the present study, we compared the effects of the GBG-stimulus presentation (P) and GBGstimulus removal (R) on levels of disruptions in a 2nd-grade general education classroom. In addition, we measured student prompts, teacher praise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The findings of our study can provide one more argument for the short-term effectiveness of GBG, as signaled by many previous researchers (Medland & Stachnik, 1972;Coombes et al, 2016;Groves & Austin, 2017). It also is in line with previous studies on the implementation of the GBG in various cultural contexts and countries as different as the USA, Estonia, and Sudan (Silva & Wiskow, 2020;Saigh & Umar, 1983). Even in relation to studies on modifying the GBG for new technologies like ClassDojo or Class Badges (Dadakhodjaeva, 2017;Dillon, 2016;Ford, 2017;Vargo & Brown, 2020), the findings of our study prove that the sudden shift to online education under the COVID-19 pandemic did not mean the GBG was no longer applicable.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of our study can provide one more argument for the short-term effectiveness of GBG, as signaled by many previous researchers (Medland & Stachnik, 1972;Coombes et al, 2016;Groves & Austin, 2017). It also is in line with previous studies on the implementation of the GBG in various cultural contexts and countries as different as the USA, Estonia, and Sudan (Silva & Wiskow, 2020;Saigh & Umar, 1983). Even in relation to studies on modifying the GBG for new technologies like ClassDojo or Class Badges (Dadakhodjaeva, 2017;Dillon, 2016;Ford, 2017;Vargo & Brown, 2020), the findings of our study prove that the sudden shift to online education under the COVID-19 pandemic did not mean the GBG was no longer applicable.…”
Section: Discussionsupporting
confidence: 92%
“…There have not been very many studies and reflections on the GBG implementation process as such, especially in regard to introducing it for the first time in a whole education system and with a large number of pupils. Two recent exceptions stand out: a study by Silva and Wiskow (2020) who examined teachers' performance and adherence to the rules, and Streimann et al (2020), who studied the implementation of the PAX GBG in Estonian schools. What we mean by the implementation process is a structural intervention on a large social scale and with a potentially extensive impact on the education system in a given society.…”
Section: Anna Kwatera Mariusz Dzięglewski Implementation Of the Good ...mentioning
confidence: 99%
“…Of these five experiments, fidelity was an independent variable in two (St. Peter et al, 2016, Experiments 1 and 2), and the reported fidelity scores corresponded to the programmed levels of reduced fidelity. The others consisted of teacher implementation of the Good Behavior Game (Donaldson et al, 2011, 60% fidelity; Foley et al, 2019, 72% fidelity; Silva & Wiskow, 2020, 67% fidelity).…”
Section: Resultsmentioning
confidence: 99%
“…So long as fidelity data are collected well, lower fidelity coupled with changes in the dependent variable(s) may provide evidence of the potency of an intervention or suggest components that could be reduced or removed. For example, studies on the Good Behavior Game demonstrate consistent improvements in child outcomes even when fidelity scores are relatively low (see Donaldson et al, 2011, 60% fidelity; Foley et al, 2019, 72% fidelity; Silva & Wiskow, 2020, 67% fidelity, for examples). Therefore, we suggest that all experiments report fidelity data no matter the value.…”
Section: Discussionmentioning
confidence: 99%
“…The GBG requires relatively low effort to implement (Maag, 2019); however, implementing the game involves several additional steps beyond most standard lessons, which may increase the response effort required. One challenge for teachers can be accurately keeping score while simultaneously teaching a lesson (e.g., Donaldson et al, 2011; Joslyn & Vollmer, 2020; Silva & Wiskow, 2020; Sy et al, 2016). A potential method to reduce effort associated with teacher implementation and improve scoring accuracy may be for students to lead the game.…”
mentioning
confidence: 99%